UMPSA lecturer leads LRGS grant worth RM1.4 million - Wallid Wahidi, Hamzah (UMPSA, 2025)
NILAI, 3 October 2025 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) lecturer, Associate Professor Ts. Dr. Muhammad Aizzat Zakaria from the Faculty of Manufacturing and Mechatronic Engineering Technology (FTKPM), successfully received a Long-Term Research Grant Scheme (LRGS) from the Ministry of Higher Education (MOHE) amounting to RM1.4 million.